Prevalence and subtypes of Blastocystis in wild rodents from three provinces in China - Gao, Zhen-Qiu; Wang, Hai-Tao; Hou, Qing-Yu; Qin, Ya; Yang, Xing; Zhao, Quan; Ma, He (Frontiers in Veterinary Science, 2024)
Blastocystis is one of the most critical intestinal protozoans in various hosts, including humans and mice. To determine the status of Blastocystis infection in wild rodents in China, a total of 346 faecal samples were collected from seven wild rodent species from three provinces, and the small subunit ribosomal RNA (SSU rRNA) genes of Blastocystis were amplified to determine their prevalence and subtypes. Of the 344 samples, 54 (15.70%) were detected as Blastocystis-positive. The prevalence of Blastocystis was 26.14% (40/153), 7.95% (7/88), and 6.80% (7/103) in wild rodents from Hunan Province, Yunnan Province, and Guangxi Province, respectively. The prevalence of Blastocystis in different wild rodent species varied from 0.00% (0/13) in Mus musculus to 40.00% (2/5) in Rattus rattus sladeni. The prevalence of Blastocystis in samples from the lake beach area (27.40%, 40/146) was significantly higher than in those from the mountain (6.80%, 7/103) and field regions (7.37%, 7/95). The prevalence in different seasons was 26.14% in summer (40/153), 7.95% in autumn (7/88), and 6.80% in winter (7/103). Moreover, a total of two Blastocystis subtypes were identified in the investigated wild rodents, including ST4 and ST5. The present study discovered the existence of Blastocystis infection in Rattus favipectus, Microtus fortis, Apodemus agrarius, Bandicota indica, Rattus rattus sladeni, and Rattus losea, expanding the host range of this parasite. The findings also demonstrate that wild rodents may be an important potential infection source for Blastocystis infection in humans and other animals.